Development Strategy based on Potential Ecotourism Feasilibity in Hutan Bambu Alu, West Sulawesi - Ritabulan Ritabulan; Tasmin Tasmin; Daud Irundu; Qaizar K; Ihsan Arham (Jurnal Penelitian Kehutanan BONITA, 2023)
The Hutan Bambu Alu (Alu Bamboo Forest) is one of the tourist destinations with the characteristics of a mountainous area that has the potential to be developed with the concept of ecotourism in Polewali Mandar Regency, West Sulawesi. This study aims to calculate the potential value of attractiveness, accessibility, conditions around the area, accommodation and supporting facilities for Alu Bamboo Forest ecotourism. The results showed that Alu Bamboo Forest was feasible to be developed into an ecotourism area with a feasibility index of 79.43%. The potential-based development strategy that needs to be carried out is to carry out regular maintenance of the area, carry out area arrangements based on the level of awareness and sensitivity of the area, add alternative accommodation services, develop/create tour packages that are integrated with the area around the Alu Bamboo Forest, and build networks that both with transportation service providers to improve service quality including visitor comfort.